Micro Analysis of Yield Gap and Associated Constraints in Adoption of Wheat (Triticum aestivum L. emend. Fiori & Paol) Production Technologies in Bihar - Kumbhare, N. V.; Kumar, Anil; Singh, K.; Chowdhuary, S. (Indian Journal of Extension Education, 2012)
The present study for on-farm assessment of wheat (Triticum aestivum L. emend. Fiori & Paol) production technology  was carried out in two purposively selected wheat-growing districts, i.e. Samastipur and Muzaffarpur districts of Bihar. A stratified random sampling technique was followed to further choose the blocks, villages and respondents. Atotal of eight  villages were drawn randomly from four blocks, i.e. two villages from each of two blocks of Samastipur (Kalyanpur and  Samastipur) and Muzaffarpur (Sakra and Muzaffarpur) districts were selected. Thirty respondents were selected  randomly from each of the sampled eight villages. Thus, a total of 240 respondents from two districts constituted the  sample for the study. The findings revealed that 67.50 per cent respondents had fully adopted high-yielding varieties of  wheat, which were suitable for north-eastern plains zone. The lower technology index, in 'PBW 343' (17.56 %) was  observed when farmers used bio-fertilizer (Azatobacter + Phosphate Solubilizing Bacteria) in wheat followed by 'HD  2733' (21.81 %) under improved variety demonstration. The higher technology index of variety 'HD 2733' (35.27 %) and  'PBW 343' (34 %) under zero tillage condition was observed. The perceived constraints limiting the wheat production  were non-availability of quality seeds of High-Yielding Varitey at proper time (78.75 %), followed by high cost of  fertilizers (64.16 %) and late sowing of wheat (62.91 %).
Keywords: Assessment; adoption; technology gap; technology index